"The Rain It Takes to Learn the Limits of the Self": Wetness, Masculinity, and Neoliberal Erotics in Andrew McMillan's Playtime. (1st March 2021) - Hauck, Nicholas
Abstract: Andrew McMillan's poetics dissects the physical minutiae of love and desire, enacting ex post facto a sexual and sexualized innocent pleasure. The scenes play out places such as classrooms, trains, locker-rooms, phone booths, and attic bedrooms, and often reference liquids. Tears, sweat, rain, rivers, blood, and sperm are associated with loss and mourning, a wet erotic (childhood) innocence remembered from a dry(er) perspective of experience and awareness of masculinity. In a post-Thatcher neoliberal framework, McMillan explores scenes of masculinity. Playtime is divided into two parts; if these two parts can be provisionally labeled "before" and "after"—a facile distinction between innocence and experience—McMillan's style and form break down this narrative and open up to fluidity, questioning the possibilities of pleasure (in)formed by neoliberal ideals.